Uma abordagem ontológica baseada em informações de contexto para representação de conhecimento de monitoramento de sinais vitais humanos - Bastos, Alexsandro Beserra (2013)
Monitoring vital signs in intensive care units (ICU) is an everyday activity of various health professionals, including doctors, nurses, technicians and nursing assistants. In most ICUs, monitoring and recording vital signs are performed in a manual fashion and in predefined time instants. The records of measurements of vital signs in ICUs are generally written on preprinted forms, and a health professional has to re-sort those forms when he wants to get some information about the clinical state of a patient. Besides, when an abnormal measurement of vital sign is detected, a multiparameter monitor triggers audible alarms, and that alarm may not be prompted detected by the medical staff, depending on the workflow within an ICU. In that sense, this work proposes a knowledge representation model of monitoring of vital signs of patients in ICUs. The model proposed exploits the expressiveness and the formality of ontologies, rules and semantic web technologies. This promotes the consensual comprehension, the sharing and the reuse of vital signs of patients. The aim is to develop context-aware applications for monitoring human vital signs, including the storage, query support and semantic alarms triggering.